Karakteristik Sensorik Cookies Sweet Potasoy dengan Substitusi Tepung Ubi Jalar Ungu (Ipomoea Batatas L. Lamb) dan Tepung Kedelai (Glisine Max) Sebagai Alternatif Makanan Selingan bagi Penyandang Diabetes Melitus Tipe 2 - Suhaema, Suhaema; Adiyasa, I Nyoman; haryani, neny (Student Journal Nutrition (SJ Nutrition), 2024)
Background: Diabetes Mellitus (DM) is a global health issue that can lead to severe complications, including cardiovascular disease, neuropathy, and retinopathy. The rising incidence of DM is often linked to unhealthy dietary habits and lifestyle choices. Recent studies indicate that consuming foods high in soluble fiber can improve glycemic control by slowing glucose absorption. Objective: This study aims to evaluate the sensory characteristics of "Sweet Potasoy" cookies as an alternative snack for individuals with type 2 diabetes mellitus. Research Methods: The study employed a pre-experimental design, utilizing a hedonic sensory test conducted by 20 untrained panelists outpatient patients diagnosed with DM. Research Result: The findings reveal that 85% of panelists strongly liked the color of cookies P3. For taste, 30% of panelists strongly liked P3, while 65% indicated they liked it. Additionally, 90% of panelists preferred the texture of P3, rating it as liked or enormously liked, with all panelists providing ratings of liked or enormously liked for product P3. Conclusion: Overall, cookies P3 emerged as the most favored product across all evaluated parameters, followed by P2 and P1.